The effects of varying maternal dietary fat quantity and composition on disease programming in the offspring: a focus on essential fatty acids - Draycott, Sally Anne Victoria (2020)
The nutritional environment that an individual is exposed to during development has been shown to affect growth and fat deposition as well as disease risk in later life. In particular, the effects of a maternal diet high in fat are relatively well characterised in animal models and are typically associated with a range of offspring phenotypes, including high blood pressure, increased adiposity and impaired insulin and glucose homeostasis. These high-fat diets often contain high amounts of saturated fatty acids (SFA), however, changes in dietary recommendations over the past 60 years have resulted in increased consumption of vegetable oils. As such, dramatic increases in the intake of omega-6 polyunsaturated fatty acids (PUFA), specifically linoleic acid (LA), have been observed in Western populations. This increase in omega-6 fatty acid consumption has not been matched by an increase in the intakes of omega-3 fatty acids, which has remained stable over this period of dietary change. The effect of this dietary pattern on offspring risk of obesity and cardiometabolic disturbance is yet to be established, however, studies have demonstrated a pro-adipogenic effect of omega-6 fatty acids suggesting increases in the intake of LA may be linked to the increasing prevalence of obesity.